Pelatihan Diversifikasi Jamur Tiram Sebagai Produk Olahan Makanan di Kecamatan Pamboang Kabupaten Majene - Gaby Maulida Nurdin; Ariandi Ariandi; Muhammad Arhim (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2022)
Most areas in the Pamboang sub-district have a hilly and mountainous topography with a tropical solar climate. The fertile natural conditions are very supportive making it a potential area for agriculture and as a place for mushroom cultivation. Urawa oyster mushrooms are the first group that is productive in developing oyster mushrooms in Majene Regency. However, the number of oyster mushrooms produced is not in line with public demand. The indigenous people of Majene are still unfamiliar with the processing and taste of oyster mushrooms. This community service campaign aims to introduce oyster mushrooms as a diversification of processed food. The method of community service activities uses counseling, training and mentoring methods. This activity was attended by 30 participants from the general public, 2 traditional leaders, and 10 students of the Biology Education study program at the University of West Sulawesi. The training activity was carried out by involving all participants in making various processed oyster mushrooms such as crispy mushrooms, meatballs, nuggets, crackers, and shredded. These processed products can be stored for a long time, are practical, and are in the form that popular among the public. In addition, assistance is carried out in obtaining Urawa product P-IRT permits at the health office. Diversification of processed mushroom products will greatly help increase the marketing of oyster mushrooms and help the partner's economy as a creative business. The implementation of the activities was very good as indicated by the increase in the knowledge and skills of the participants before and after the training.